ON THE DIFFERENT AGES OF RHYOLITES (ALBITOPHYRES) AND MULTI-STAGE CHARACTER OF MINERALIZATION OCCURRENCES IN ALAVERDI ORE DISTRICT (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The paper considers questions of the geological position and age of cutting bodies of rhyolites (albitophyres). The new data we obtained allow us to consider rhyolite bodies as units having different ages, among which it is possible to identify the Bajocian, the Late Jurassic-Early Cretaceous, and the Late Eocene ones (identified by us for the first time in Zhang and Koroukh boundary areas having the absolute age estimation of $42–46~Ma$). Considering the relationship between rhyolites and copperpyrite ores, we consider copper-pyrite ores, as contrary to earlier works and opinions, as formations of an earlier age than rhyolites based on the evidence of multiple xenoliths of copper-pyrite ores present in rhyolites. On the other hand, the polymetallic ores cut through the rhyolite bodies attesting the actual time gap, separating copper-pyrite ores from poly-metallic ores, and the multi-stage character of the mineralization.
Keywords: geological position; age of cutting bodies; riolit; Bajocian; Late Jurassic-Early Cretaceous; Late Eocen